Homocysteine, Folic Acid, Cyanocobalamin, and Frailty in Older People: Findings From the “Invece. Ab” Study - Guaita, Antonio; Brunelli, Laura; Davin, Annalisa; Poloni, Tino Emanuele; Vaccaro, Roberta; Gagliardi, Stella; Pansarasa, Orietta; Cereda, Cristina (Frontiers in Physiology, 2021)
Frailty is an important age-related syndrome associated with several adverse health outcomes. Its biological basis is undefined. Raised plasma homocysteine (HOcy) is an established risk factor for cardiovascular disease, dementia, cognitive impairment, and mortality, but little is known about the possible role of plasma HOcy, cyanocobalamin (B12), and folate (FO levels in the development of frailty. Our first aim was to explore the possible association between frailty and plasma concentrations of HOcy, FO, and B12 in a cohort of community-dwelling older people. The second was to assess the influence of these metabolic factors on the six-year incidence of frailty in the 875 individuals eligible for inclusion in this study (those with a full follow-up dataset). This research is based on data from three waves — 2012 (herein taken as baseline), 2014 and 2018 — of a longitudinal study (InveCe.Ab) in which non-frail men and women born between 1935 and 1939 underwent multidimensional assessments. Frailty was estimated using a deficit accumulation-based frailty index (FI). HOcy concentration was significantly positively correlated with FI at all timepoints, while B12 and FO levels were not. Plasma concentration of HOcy emerged as a predictor of six-year cumulative incidence of frailty, independent of age, sex and education, while B12 and FO levels showed no relationship with frailty incidence. Individuals with plasma HOcy in the top quintile showed five months less frailty-free survival (HR 1.487; 95% CI: 1.063–2.078), regardless of age, sex and education. These results demonstrate that higher HOcy is a risk factor for frailty onset in older adults.